Dynamic Sliding Characteristics of Synchronous Meshing of Thread Pairs and Gear Pairs of the Planetary Roller Screw Mechanism - Zhang Jianxin; Ma Shangjun; Deng Wenzhu; Ma Tenglong; Liu Geng (Jixie chuandong)
To reveal the dynamic sliding characteristics of synchronous meshing of thread pairs and gear pairs of the planetary roller screw mechanism, a calculation method for the sliding angle of the planetary roller screw mechanism was proposed, and a numerical model of the planetary roller screw mechanism was established to verify the correctness of the sliding angle calculation method. Firstly, based on the mechanism of the pitch circle offset, the kinematics analysis model of the slip angle was established, and its correctness was verified by comparing with the numerical solution. On this basis, the influences of the screw speed, nut load on the sliding angle and the sliding distance of thread gear and gear pairs were analyzed. The research results indicate that the sliding angle increases with the increase of the screw speed and the nut load. The sliding distance on the roller screw side is much greater than that on the roller nut side, and both increase with the increase of the screw speed and the nut load. The sliding distance of the gear pair decreases with the increase of the screw speed and increases with the increase of the nut load.